Addressing ageism : be active in aging: study protocol - Fernandes, Júlio Belo (2022)
Ageism refers to stereotyping (how we think), prejudice (how we feel), and discrimination (how we act) against people based on their age. It is a serious public health issue that can negatively impact older people’s health and quality of life. The present protocol has several goals: (1) adapt the Ambivalent Ageism Scale for the general Portuguese population and healthcare professionals; (2) assess the factorial invariance of the questionnaire between general population vs. healthcare professionals; (3) evaluate the level of ageism and its predictors in the general population and evaluate the level of ageism and its predictors in healthcare professionals; (4) compare the levels of ageism between groups and the invariance between groups regarding the explanatory model of predictors of ageism. This quantitative, cross-sectional, descriptive, observational study will be developed in partnership with several Healthcare Professional Boards/Associations, National Geriatrics and Gerontology Associations, and the Universities of the Third Age Network Association. The web-based survey will be conducted on a convenience sample recruited via various social media and institutional channels. The survey consists of three questionnaires: (1) Demographic data; (2) Ambivalent Ageism Scale; (3) Palmore-Neri and Cachioni questionnaire. The methodology of this study will include translation, pilot testing, semantic adjustment, exploratory and confirmatory factor analysis, and multigroup analysis of the Ambivalent Ageism Scale. Data will be treated using International Business Machines Corporation (IBM®) Statistical Package for the Social Sciences (SPSS) software and Analysis of Moment Structures (AMOS). Descriptive analysis will be conducted to assess the level of ageism in the study sample. The ageism levels between the two groups will be compared using the t-student test, and two Structural Equation Modeling will be developed to evaluate the predictors of ageism. Assessing ageism is necessary to allow healthcare professionals and policymakers to design and implement strategies to solve or reduce this issue. Findings from this study will generate knowledge relevant to healthcare and medical courses along with anti-ageism education for the Portuguese population.